Impact of the Shape of the Needle Tip on the Efficacy of Flushing Implantable Port Chambers. Issue 6 (November 2016) - Guiffant, Gérard; Dupont, Christian; Merckx, Jacques
Introduction: To follow international guidelines and protect healthcare workers from needle stick injuries, manufacturers now provide safety non-coring needles. Methods: Numerical simulations show the potential efficacy of infusion and flushing flow in straight and curved side wall port chambers from a beveled non-coring needle (BNCN) or a bevel-free cannula (BFC). Results: In straight and curved side wall port chambers, the stream of flow with a BNCN is determined by the direction of the bevel, whereas the outlet stream from a BFC leads to a cylindrical symmetric flow. This, along with the position of the BFC impacts the wall shear rate of the port chamber, and the hydraulic resistance within the chamber. Discussion: This last factor has never been the subject of extensive hydrodynamic study. Caregiver safety and patient comfort are paramount but physics show that the shape of the needle tip affects the hydrodynamics of the injected flow. Conclusions: The presence of a bevel at the needle tip is a key factor for ensuring efficient flushing of the port. The absence of a bevel may increase hydraulic resistance and deposits in the port chamber. Implantable port flushing protocols must take this notion into account if the patency of port chambers is to be maintained. The clinical impact of this study has yet to be determined.